Robust adaptive geometric tracking controls on SO(3) with an application to the attitude dynamics of a quadrotor UAV - Fernando, T.; Chandiramani, J.; Taeyoung Lee; Gutierrez, H. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
This paper provides new results for a robust adaptive tracking control of the attitude dynamics of a rigid body. Both of the attitude dynamics and the proposed control system are globally expressed on the special orthogonal group, to avoid complexities and ambiguities associated with other attitude representations such as Euler angles or quaternions. By designing an adaptive law for the inertia matrix of a rigid body, the proposed control system can asymptotically follow an attitude command without the knowledge of the inertia matrix, and it is extended to guarantee boundedness of tracking errors in the presence of unstructured disturbances. These are illustrated by numerical examples and experiments for the attitude dynamics of a quadrotor UAV.